Jurisdictional Transformation of Government Liability Disputes in Indonesia: The Role of the Tax Court - Budi Haritjahjono; KMS Herman (Greenation International Journal of Law and Social Sciences, 2025)
The transformation of governance in Indonesia can be traced through the shifting jurisdiction over disputes involving unlawful acts by the government (onrechtmatige overheidsdaad). Initially adjudicated by the General Courts under the paradigm of private law, these disputes were later reassigned to the Administrative Court following the enactment of Law No. 5 of 1986, reflecting the recognition of government actions as matters of public law. In the strategic field of taxation, Indonesia further established a specialized judicial body, the Tax Court under Law No. 14 of 2002, designed to address the complex, interdisciplinary nature of tax disputes, which involve not only law but also economics, accounting, and public policy. This article aims to analyze the role of the Tax Court in strengthening governance by ensuring accountability, transparency, and fairness in the resolution of government liability disputes. The study employs a normative juridical approach combined with comparative insights to explore the evolving jurisdictional framework. The findings indicate that the Tax Court’s authority extends beyond the narrow scope of tax collection, encompassing a broader mandate to uphold legal certainty and public trust in fiscal administration. By situating tax adjudication within the context of global governance and welfare, the Tax Court contributes to aligning domestic legal practices with international standards, thereby reinforcing Indonesia’s commitment to good governance. The conclusion underscores that jurisdictional transformation in government liability disputes not only redefines institutional arrangements but also strengthens interdisciplinary synergy between law and economics, fostering global welfare through improved accountability mechanisms.